2017
DOI: 10.3233/ch-168034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of magnetic resonance imaging (MRI) and contrast-enhanced ultrasound (CEUS) in the evaluation of unclear solid renal lesions

Abstract: CEUS is an useful method which can be additionally used to clinically differentiate between malignant and benign renal lesions. CEUS shows a comparable sensitivity, specificity, PPV and NPV to MRI. In daily clinical routine, patients with contraindications for other imaging modalities can particularly benefit using this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Six of the 16 included studies were cohort studies [17][18][19][20][21][22] and 10 were descriptive studies [23][24][25][26][27][28][29][30][31][32]; none were RCTs ( Table 1).…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of the 16 included studies were cohort studies [17][18][19][20][21][22] and 10 were descriptive studies [23][24][25][26][27][28][29][30][31][32]; none were RCTs ( Table 1).…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…These results suggest that CEUS is superior to CEMR in the diagnosis of complex CRMs in terms of abovementioned parameters of diagnostic performance. Furthermore, Rübenthaler et al [27] found that CEUS can be used to clinically differentiate between benign and malignant RMs. In their study involving 36 unclear solid RMs, CEUS had higher DA, specificity, ROC area, PPV, and NPV than, and equal sensitivity to, CEMR.…”
Section: Findings In the Context Of Existing Evidencementioning
confidence: 99%
“…Thus, a total of 165 patients with172 renal masses were recruited, 150 (87.2%) were RCCs and 22 (12.8%) were AMLs. The RCCs were clear cell carcinoma (129, 86.0%), papillary carcinoma (11, 7.3%), chromophobe carcinoma (10,6.7%), respectively. Though age distribution, tumor location, and surgical method were not significantly different between RCCs and AMLs, more percentage of patients with RCC were male than that with AML (P=0.000).…”
Section: Characteristics Of the Enrolled Patientsmentioning
confidence: 99%
“…CEUS has unique advantages with non-ionizing, real-time imaging, and rare and mild adverse reactions induced by contrast agents [8]. The previous studies [9,10] have reported that CEUS might have a good ability to assess renal masses, but the CEUS characteristics of RCC are still controversial. Xu et al [11] found that heterogeneous enhancement was a major CEUS characteristic regardless of the subtype of RCC.…”
Section: Introductionmentioning
confidence: 99%